Department Leadership in Action: Enhancing Your Leadership and Academic Team - Dr. Walter H. Gmelch (Academic Chairpersons Conference Proceedings, 2017)
This workshop will explore four key leadership questions: what is an academic leader and why should you serve; how to develop as a leader; how long is long enough to serve; and what legacy will you leave? Participants will develop strategies for effectively developing your team through shared leadership, consensual decision-making, constructive conflict, collegiality and more. The workshop also includes a discussion of exploring the “road less traveled,” managing transitions to and from academic leadership.
Keywords: academic leader; develop; strategies; decision-making